THE JAMES B. HUNT, JR. LIBRARY. A LIBRARY FOR THE FUTURE: TODAY - M. DAY, North Carolina State University, Deanna (BIBLIOPOLIS, 2020)
Since opening in January 2013, the James B. Hunt, Jr. Library has been regarded as a library of the future. Seamlessly integrating technology with an abundance of inspiring and thought provoking study and research spaces, natural light, and sustainable features, Hunt has become a destination for thousands of visitors who want to see and experience how the library of the future looks today.